Fostering future teacher well-being : A participatory investigation in South Africa - Maree, Burgert (My University, 2024)
Teachers are under pressure. Alarming global teacher attrition rates highlight the numerous stresses that teachers face at present, and new ideas and images of the future of education are emerging and being advocated for. The space that teachers hold between the past, present and future of education, combined with their daily responsibilities warrants a concern for their present, and future, well-being. Considering teacher well-being (TWB) from a futures perspective adds to the novel nature of this multi-disciplinary research and contributes to the fields of education and futures studies. Two research questions investigate teachers’ perceptions of their own well-being and how future teacher well-being (TWB) could be fostered. A questionnaire and a Futures Workshop (FW) were used to address the research questions. The recently proposed OECD conceptual framework for TWB, which focuses specifically on teachers’ occupational well-being in their situated/school environment, guided the directed content analysis to determine how well teachers’ perceptions on their own well-being aligns with the research to date. Results indicated that teachers’ perceptions on their own well-being are well-aligned with the research to date. The future fostering of TWB, however, is a complex matter. Due to various factors, teachers seem to struggle envisioning different, preferred futures. The status quo, a probable future, becomes the default projection for the future. The development of imagination is confirmed to be vitally important in thinking about the future. TWB is highly context-sensitive, and varying results should be expected in different contexts. Whilst numerous frameworks and interventions assist in the fostering of TWB, the future fostering of TWB requires imagination, a skill that needs to be developed to assist in futures thinking. Despite contextual limitations on the results of the participatory workshop held in South Africa, the research findings do allow the results and impressions gathered to be interrogated on a global scale.
Keywords: Teacher well-being, Participatory research, Futures triangle, Futures workshop, Future images, South Africa